2015
DOI: 10.1166/jnn.2015.9633
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Study on Thermal Conductivity of Proton Exchange Membrane

Abstract: In this paper, the thermal conductivity of dry Nafion 117 is measured by Hot Disk TPS2500 and a molecular dynamics calculation model for the proton exchange membrane is constructed by Materials Studio (MS) software platform to study its thermal conductivity. Cell structures of different water content of Nafion membrane at 300 K and 330 K are obtained, respectively. It is found that at the same temperature the predicted thermal conductivity of PEM increases with the water content, and at the same water content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Among the structures, the thermal conductivity of the Nafion (m = 1, n = 2) membrane is 0.24 W • m −1 • K −1 at 300 K, which matches with the data in the literature 45…”
Section: Resultssupporting
confidence: 88%
“…Among the structures, the thermal conductivity of the Nafion (m = 1, n = 2) membrane is 0.24 W • m −1 • K −1 at 300 K, which matches with the data in the literature 45…”
Section: Resultssupporting
confidence: 88%
“…But as one of the nanoscale simulation methods, molecular dynamics (MD) simulation is a powerful tool to explore the nanoscale information in molecule level. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] And based on MD simulation, many researches have been carried out to explore the structural properties, [5][6][7][8] proton transport, [9][10][11][12][13] gas molecules transport, 4,14,15 mechanical deformation, 16,17 thermal conductivity 18,19 of PFSA membrane. For the structural properties of PFSA membrane, Liu et al 5 analyzed the relationships between structural properties and water content, equivalent weight and molecular weight of PFSA polymers.…”
mentioning
confidence: 99%
“…Furthermore, the thermal conductivity of PFSA membrane was found to increase as water content and temperature increase by non-equilibrium molecular dynamics simulation. 18 Zheng et al 19 demonstrated that the thermal conductivity of Aciplex membrane was higher than Dow and Nafion membrane.…”
mentioning
confidence: 99%
“…In recent years, a theoretical calculation is always used to simulate the molecular's structure and the film's properties. Molecular dynamic simulations can quickly help to construct most materials' structures and provide many different models to calculate relevant information [30][31][32]. Wei et al [33] used molecular dynamic simulations to obtain the adsorption of CO 2 in some ZIF-8 analogs.…”
Section: Introductionmentioning
confidence: 99%